Dicliptera mercedesiae, a new species of the genus Dicliptera (Acanthaceae) from Peru - Villanueva-Espinoza, Rosa; Wasshausen, Dieter; Fernandez-Hilario, Robin (Phytotaxa, 2021)
Dicliptera mercedesiae (Acanthaceae: Justicieae), a new species is described and illustrated from the Junin region of Peru. The new species is similar to Dicliptera purpurascens, but differs by its subsessile flowers, smaller elliptic cymules bracts and corolla without resupination.